2019
DOI: 10.3389/fphar.2019.00501
|View full text |Cite
|
Sign up to set email alerts
|

Fast Green FCF Attenuates Lipopolysaccharide-Induced Depressive-Like Behavior and Downregulates TLR4/Myd88/NF-κB Signal Pathway in the Mouse Hippocampus

Abstract: Depression is a common neuropsychiatric disorder and new anti-depressive treatments are still in urgent demand. Fast Green FCF, a safe biocompatible color additive, has been suggested to mitigate chronic pain. However, Fast green FCF’s effect on depression is unknown. We aimed to investigate Fast green FCF’s effect on lipopolysaccharide (LPS)-induced depressive-like behavior and the underlying mechanisms. Pretreatment of Fast green FCF (100 mg/kg, i.p. daily for 7 days) alleviated depressive-like behavior in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 42 publications
1
28
0
2
Order By: Relevance
“…Previously, studies have shown that the interaction of CD14, a glycosylphosphatidylinositol-anchored monocytic antigen, with TLR4 is an early event of neuroinflammation signaling activation [46]. Additionally, upon LPS binding, CD14 associates with the extracellular domain of TLR4, which in turn activates the TLR4 intracellular domain-mediated signaling complex including MyD88, IRAK, and TRAF, leading to downstream signal transduction through NF-κB-mediated inflammatory cascades [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies have shown that the interaction of CD14, a glycosylphosphatidylinositol-anchored monocytic antigen, with TLR4 is an early event of neuroinflammation signaling activation [46]. Additionally, upon LPS binding, CD14 associates with the extracellular domain of TLR4, which in turn activates the TLR4 intracellular domain-mediated signaling complex including MyD88, IRAK, and TRAF, leading to downstream signal transduction through NF-κB-mediated inflammatory cascades [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The RT-PCR analysis was performed as previously described (Yang et al, 2019). Four weeks after CUMS, our control mice were deeply anesthetized with an overdose of sodium pentobarbital (150 mg/kg i.p.)…”
Section: Real-time Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…However, after the resolution of sickness behavior, the rodents persistently display depressive-like behaviors, indicated by increased immobility in the forced swimming test (FST) and anhedonia in the sucrose preference test (SPT) [ 36 , 38 , 39 , 40 ]. It has been proposed that neuroinflammation-related activation of TLR4/Myd88/NF-κB signaling pathway in the hippocampus might play an important role in partially mediating LPS-induced depression-like behaviors [ 41 , 42 ]. Several reports have supported the notion that inhibiting cytokine release and/or interrupting the TLR4/Myd88/NF-κB signaling pathway may be effective in reducing the magnitude of LPS-induced depression-like behavior, but not LPS-induced sickness [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that neuroinflammation-related activation of TLR4/Myd88/NF-κB signaling pathway in the hippocampus might play an important role in partially mediating LPS-induced depression-like behaviors [ 41 , 42 ]. Several reports have supported the notion that inhibiting cytokine release and/or interrupting the TLR4/Myd88/NF-κB signaling pathway may be effective in reducing the magnitude of LPS-induced depression-like behavior, but not LPS-induced sickness [ 42 , 43 , 44 ]. Taken together, the results of these studies have two major implications.…”
Section: Introductionmentioning
confidence: 99%